'It has become everybody's business and nobody's business': Policy actor perspectives on the implementation of TB infection prevention and control (IPC) policies in South African public sector primary care health facilities. Issue 10 (3rd October 2021) - Colvin, Christopher J.; Kallon, Idriss I.; Swartz, Alison; MacGregor, Hayley; Kielmann, Karina; Grant, Alison D.
ABSTRACT: South Africa is increasingly offering screening, diagnosis and treatment of tuberculosis (TB), and especially drug-resistant TB, at the primary care level. Nosocomial transmission of TB within primary health facilities is a growing concern in South Africa, and globally. We explore here how TB infection prevention and control (IPC) policies, historically focused on hospitals, are being implemented within primary care facilities. We spoke to 15 policy actors using in-depth interviews about barriers to effective TB-IPC and opportunities for improving implementation. We identified four drivers of poor policy implementation: fragmentation of institutional responsibility and accountability for TB-IPC; struggles by TB-IPC advocates to frame TB-IPC as an urgent and addressable policy problem; barriers to policy innovation from both a lack of evidence as well as a policy environment dependent on 'new' evidence to justify new policy; and the impact of professional medical cultures on the accurate recognition of and response to TB risks. Participants also identified examples of TB-IPC innovation and described conditions necessary for these successes. TB-IPC is a long-standing, complex health systems challenge. As important as downstream practices like mask-wearing and ventilation are, sustained, effective TB-IPC ultimately requires that we better address the upstream barriers to TB-IPC policy formulation and implementation.